Does Zakat and Non-Zakat Empowerment Affect Mustahiq Welfare Based on Maqashid Shariah? - Tika Widiastuti; Ilmiawan Auwalin; Lina Nugraha Rani; Imron Mawardi; Muhammad Ubaidillah Al Mustofa; Norma Rosyidah; Siti Nur Mahmudah (Universitas Negeri Surabaya, 2021)
This study explores the effect of zakat and non-zakat empowerment programs on the beneficiaries' welfare (mustahiq). This study focuses on the influence of the intervening variable, namely the mustahiq businesses' growth on mustahiq welfare. This study also examines the role of demographic characteristics, such as age, gender, and years of education on mustahiq business growth. This study employs the Partial Least Square-Structural Equation Model (PLS-SEM) using data from 100 respondents who received empowerment assistance from three different zakat institutions. The sample of mustahiq was selected from three zakat institutions to provide a diversity of respondents. The results indicate that zakat and non-zakat programs' empowerment through business growth has significantly affected mustahiq welfare. With these results, both zakat and non-zakat productive programs should be more developed to assist the community businesses' growth optimally. Previous studies measure the welfare of mustahiq with material aspects. In this study, the indicator of welfare is based on maqashid sharia, which includes the protection of Ad-Din (religion), An-Nafs (Soul), Al-Aql (intellect), Al-Nasl (descendant), and Al-Maal (wealth). Examining the impact of two variables, namely productive empowerment programs through zakat and non-zakat, on mustahiq business growth and welfare is the novelty of this study.